Cube Root

Algebra Level 3

99 70 2 \large 99-70\sqrt2

If the cube root of the expression above can be written in the form a + b c a+b\sqrt{c} , where a a , b b , and c c are integers,and c c is square-free, then what is the value of a + b + c a+b+c ?


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Jan 10, 2018

Given that:

a + b c = 99 70 2 3 Cubing both sides a 3 + 3 a 2 b c + 3 a b 2 c + b 3 c c = 99 70 2 \begin{aligned} a+b\sqrt c & = \sqrt[3]{99-70\sqrt 2} & \small \color{#3D99F6} \text{Cubing both sides} \\ a^3+3a^2b\sqrt c + 3ab^2c + b^3c\sqrt c & = 99-70\sqrt 2 \end{aligned}

Equating the rational and irrational parts:

{ a 3 + 3 a b 2 c = 99 . . . ( 1 ) ( 3 a 2 b + b 3 c ) c = 70 2 . . . ( 2 ) \begin{cases} a^3 + 3ab^2c = 99 & ...(1) \\ \left(3a^2b + b^3c\right)\sqrt c = -70\sqrt 2 & ...(2) \end{cases}

It is reasonable to assume that c = 2 \sqrt c = \sqrt 2 , c = 2 \implies c=2 and the two equations become:

{ a ( a 2 + 6 b 2 ) = 99 . . . ( 1 ) b ( 3 a 2 + 2 b 2 ) = 70 . . . ( 2 ) \begin{cases} a\left(a^2 + 6b^2\right) = 99 & ...(1) \\ b\left(3a^2 + 2b^2\right) = -70 & ...(2) \end{cases}

From ( 1 ) : a ( a 2 + 6 b 2 ) = 3 2 × 11 (1): a\left(a^2 + 6b^2\right) = 3^2 \times 11 , since a a and b b are integers, a a can only be 1, 3, 9, 11, 33, and 99. Then we have:

{ a = 1 b = 98 6 No integral solution a = 3 b = ± 2 Integral solution a = 9 No real solution No real solution for a > 5 \begin{cases} a = 1 & \implies b = \sqrt {\dfrac {98}6} & \small \color{#D61F06} \text{No integral solution} \\ a = 3 & \implies b = \pm 2 & \small \color{#3D99F6} \text{Integral solution} \\ a = 9 & \implies \small \color{#D61F06} \text{No real solution} & \small \color{#D61F06} \text{No real solution for }a > 5 \end{cases}

From ( 2 ) : b ( 3 a 2 + 2 b 2 ) = 70 (2): b\left(3a^2 + 2b^2\right) = -70 , we note that b < 0 b<0 , since 3 a 2 + 2 b 2 > 0 3a^2 + 2b^2 > 0 . Therefore, b = 2 b=-2 . Substituting a = 3 a=3 and b = 2 b=-2 in ( 2 ) : 2 ( 3 ( 3 2 ) + 2 ( 2 ) 2 ) = 70 (2): -2\left(3(3^2) + 2(-2)^2\right) = - 70 . Therefore, the solution ( a , b , c ) = ( 3 , 2 , 2 ) (a,b,c) = (3,-2,2) is valid and a + b + c = 3 a+b+c = \boxed{3} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...